Feasibility of solar adsorption air-conditioning in the region of Biskra: Reflection on the government support for electricity bills - Benfatah, Hocine; Benchabane, Adel; Rouag, Amar; Labed, Adnane (Journal of Applied Engineering Science & Technology, 2018)
In this paper, the feasibility of solar adsorption air conditioning system in the region of Biskra (Algeria) is studied. The main objective is to give a reflection on the current government support for electricity bills. A comparison between three air conditioning systems was made by taking into account economic and environmental constraints: classical mono-split system (A), classical centralized air conditioning chiller (B) and solar adsorption system (C). In the context of the current government support for electricity bills, results show that system A is actually the best choice from the total investment costs, electrical consumption and maintenance point of view. This is observed even with the gain of the electrical consumption obtained in the case of solar adsorption air conditioner (C). From an environmental point of view, the system (C) is more advantageous than the classical systems (A) & (B) especially for its use of the solar energy, its low electrical consumption, low CO2 emissions and low heat rejected to the outside. It can be concluded that the current state policy do not encourage the transition to the use of air conditioning systems operate by renewable energies. Thus, the redirection of the current support for electricity bills to the support of the investment cost of the solar adsorption air conditioner (C) will make it more competitive in the Algerian market. In this case, system (C) can replace, in the long-term, the system (A) used actually.